Influence of Work Factors, Emotional Demands, and Organizational Demands on Physical and Mental Fatigue in the Disaster Preparedness Workers - Bian Shabri Putri Irwanto (Pusat riset dan Inovasi Nasional, 2025)
Regional Disaster Management Agency (RDMA) workers must be on standby and respond for 24 hours, especially if there are emergency. This causes demands on workers and workers become fatigue. The aim of this study is to analyze the factors that influence work fatigue in Tuban Regency’s RDMA workers. This research includes analytical and observational with a cross sectional design. The study was conducted on 56 workers with a simple random sampling system. The dependent variable studied was physical and mental fatigue, while the independent variables consisted of work factors (working hours and workload), emotional demands (responsibility), and organizational demands (work shifts). Data collection was carried out by direct measurement, questionnaires, interviews, documentation and observation then processed with Structural Equation Modeling-Partial Least Square (SEM-PLS). The factors that affect work fatigue are work factors (t statistics = 3.643 and p-values = 0.000) and organizational demands (t statistics = 3.086 and p-values = 0.002), while emotional demands have no effect (t statistics = 0.950 and p-values = 0.342). Loading factors of physical work fatigue (0.917) and mental work fatigue (0.916) are almost the same, so they have the same contribution as a measure of fatigue. Workers who experience work fatigue should conduct regular medical examinations, know the workload limit for one day, organize sufficient work time, regularly rotate work time, stretch in the middle of work activities, prepare work music and videos during breaks.